Investigation of pulp flow helicity in rotating and non-rotating grooves. (December 2021) - Jouybari, Nima F; Engberg, Birgitta; Persson, Johan; Berg, Jan-Erik
Numerical simulation of pulp flow in rotating and non-rotating grooves is carried out to investigate the effect of pulp rheological properties and groove geometry on the rotational motion of the pulp flow. The eucalyptus pulp suspension is considered as a working fluid in the present study whose apparent viscosity correlation is available from the experimental measurements reported in the literature. The simulations are carried out with OpenFoam for different values of pulp material, fiber concentrations, and groove cross-section. Helicity is introduced to measure the turnover rate of pulp flow in the groove due to the importance of such motion on the final properties of the pulp flow. A measurement of helicity magnitude and its distribution along the groove revealed that a change in the pulp material would significantly affect the flow structures within the groove. Further investigation on the effects of fiber concentration, c, showed that this parameter does not have a significant effect on the averaged helicity magnitude for c = 2.0 and 2.5, whereas the helicity distribution over the groove cross-section changes clearly for c = 1.5. The results showed that the helicity level is negligible for almost half of the cavity cross-section in the non-rotating groove simulations, which can be considered as a shortcoming of the original geometry of the groove. Therefore, a smaller cross-section for the groove is considered through which an enhancement in the helicity magnitude is observed.